2020
DOI: 10.3389/fonc.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiochemotherapy on Immune Cell Subtypes in High-Grade Glioma Patients

Abstract: Glioblastoma is a dreadful disease with very poor prognosis, median overall survival being <2 years despite standard-of-care treatment. This has led to the development of alternative strategies, among which immunotherapy is being actively tested. In particular, many clinical trials of therapeutic vaccination using peptides or tumor cells are ongoing. A major issue in implementing therapeutic vaccines in patients with high-grade glioma is that immune responses have to be elicited in the context of immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…General blood counts and immune cell counts and functioning, as analyzed in the routine clinical laboratory, are shown in Figure 2 A. A large proportion of patients were lymphopenic at that time—caused by the radiochemotherapy—a finding compatible with published data [ 39 ].…”
Section: Individualized Multimodal Immunotherapy For Gbmsupporting
confidence: 80%
See 2 more Smart Citations
“…General blood counts and immune cell counts and functioning, as analyzed in the routine clinical laboratory, are shown in Figure 2 A. A large proportion of patients were lymphopenic at that time—caused by the radiochemotherapy—a finding compatible with published data [ 39 ].…”
Section: Individualized Multimodal Immunotherapy For Gbmsupporting
confidence: 80%
“…It is already well-known that neurosurgical removal of the tumor transiently “relieves” the systemic immune system from tumor-induced immunosuppression [ 34 ], which returns upon disease progression [ 35 ]. Both radiotherapy and TMZ have effects on inflammation and the systemic immune compartment but may also influence the tumor microenvironment [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Current Anti-cancer Treatment Strategies For Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, it is indicated that patients should be monitored for opportunistic infections [190]. Furthermore, it was demonstrated that concomitant standard radiation and TMZ (RT/TMZ) provokes a strong reduction in lymphocytes but numbers of lymphocytes slowly come back to normal when treatment with TMZ is stopped [191]. Another study showed that the frequency and absolute numbers of natural killer (NK) cells, which are known to destroy tumour cells by their ability to initiate apoptosis in target cells with reduced levels of MHC molecules ('missing-self' recognition), are decreased in RT/TMZ-treated GB patients [189].…”
Section: Experimental Limitations In the Context Of Tmz's Effect On Tmentioning
confidence: 99%
“…In a mouse model, administration of systemic bis-chloroethylnitrosourea induced lymphodepletion, decreased the number of TILs, and reduced the survival benefit from PD-1 blockade [ 186 ]. Furthermore, during concurrent chemoradiation with temozolomide, the absolute T and B cell counts were reduced and remained low even after the completion of treatment, and the composition of these immune cells shifted toward persistent increased Treg expression with concomitant decreased expression of naïve CD4+ T cells [ 187 ]. Interestingly, PD-1/PD-L1 checkpoint inhibition in temozolomide-resistant tumors also led to increased immunosuppressive macrophage infiltration in tumors [ 188 ] which was resolved by the co-administration of a PI3Kγ inhibitor.…”
Section: Molecular Mechanisms Of Resistance To Immunotherapymentioning
confidence: 99%